1995
DOI: 10.1111/j.1540-8191.1995.tb00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Declining Risk of Reoperative Valvular Surgery

Abstract: One hundred eleven patients underwent their second to fifth open heart operation, excluding isolated coronary revascularization. The procedures included repeat, single and multiple valve replacements, concomitant redo valve surgery, plus aortic root, and/or aortic arch reconstruction with or without coronary bypass graft. Six patients had heart transplantation as the final procedure. The article is based on the analysis of the experience of one surgeon with particular emphasis on technical considerations and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Reoperations in cardiac surgery are reported to be associated with an increased risk for morbidity and mortality [ 15 ]. Redo mitral valve surgery is extremely complex technically due to the necessity of re-entering the heart, dense adhesions and difficulties in exposing the valve.…”
Section: Discussionmentioning
confidence: 99%
“…Reoperations in cardiac surgery are reported to be associated with an increased risk for morbidity and mortality [ 15 ]. Redo mitral valve surgery is extremely complex technically due to the necessity of re-entering the heart, dense adhesions and difficulties in exposing the valve.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid these complications, anterolateral thoracotomy is suggested by some. 9,13,14 A minimally invasive approach via a right minithoracotomy also could present a valuable approach. This article describes our experience with this alternative method.…”
mentioning
confidence: 99%
“…Although some authors have shown that the risks of conventional reoperative valve surgery have been decreasing over the past decade [10,11], operative mortality still ranges from 9% to 24% for reoperative aortic valves and up to 14% for simple reoperative mitral valves. With the presence of coronary artery disease this operative mortality is doubled [10] and with two or more prior cardiac operations this operative mortality has been reported to be as high as 23% [12•].…”
Section: Discussionmentioning
confidence: 99%